2018
DOI: 10.3390/tropicalmed3020040
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in Bangladesh: A Clinical and Epidemiological Analysis of Culture-Confirmed Cases

Abstract: Melioidosis is known to occur in Bangladesh, but there are few reports about the condition in the published international literature. We set out to review all known cases of melioidosis in the country to date, using both retrospective and prospective data. A web-based literature search was conducted to identify all published case reports, original articles and conference abstracts. Cases were also included from a prospective study conducted in 2017. Fifty-one cases were identified between 1961 and 2017. Cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Serological survey results demonstrate a seroprevalence of 9.8% in regions with no reported clinical cases of melioidosis and a seroprevalence of 22.6 to 30.8% in regions with proven cases. Additionally, as may be expected, there is an association between the highest seroprevalence areas and number of cases (123,124). Environmental sampling isolated B. pseudomallei from only 1% of soil samples; however, the authors of this study recognize that their methods differed from the current international consensus guidelines (124,125).…”
Section: South Asiamentioning
confidence: 60%
See 1 more Smart Citation
“…Serological survey results demonstrate a seroprevalence of 9.8% in regions with no reported clinical cases of melioidosis and a seroprevalence of 22.6 to 30.8% in regions with proven cases. Additionally, as may be expected, there is an association between the highest seroprevalence areas and number of cases (123,124). Environmental sampling isolated B. pseudomallei from only 1% of soil samples; however, the authors of this study recognize that their methods differed from the current international consensus guidelines (124,125).…”
Section: South Asiamentioning
confidence: 60%
“…Environmental sampling isolated B. pseudomallei from only 1% of soil samples; however, the authors of this study recognize that their methods differed from the current international consensus guidelines (124,125). To date, cases have been described only from north and east Bangladesh, and there is no formal notification policy (123). In Sri Lanka, the first culture-confirmed case of melioidosis occurred in a European resident in 1927 (126).…”
Section: South Asiamentioning
confidence: 86%
“…10 A study from Bangladesh over a prolonged period from 1961 to 2017 noted musculoskeletal (21, 43%), organ abscess/deep-seated abscess (13, 27%), and cutaneous (13, 27%) lesions to be the predominant manifestations. 39 A study in Cambodia on pediatric melioidosis found that the infection was predominantly localized in 27 cases (69%) and disseminated in 12 (31%). 40 A point of note is that it is vital to consider melioidosis as one of the differential diagnosis in abscesses in unusual sites such as the spleen, parotid, and prostate, especially with chronic presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of resistance to conventional antibiotics by several microorganisms has further augmented the research in the case of AMPs. AMPs have played an important role as a self-defense mechanism as well as penetration enhancer for certain antibiotics (Chowdhury et al 2018 ; Fontela et al 2018 ). Many novel drug delivery systems were attempted to deliver AMPs and to reduce their resistance.…”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%